Merger as a Matter of Extrinsic Constraints - Gratz, Joseph (The Columbia Journal of Law & the Arts, 2020)
What is merger? Let’s first take a look at what the Second Circuit says merger is. The Second Circuit says merger happens “in those instances where there is only one or so few ways of expressing an idea that protection of the expression would effectively accord protection to the idea itself.”1 A situation where, if you’ve got a monopoly on a particular way of expressing something, you’ve effectively got a monopoly on that thing—and we don’t want you to have a monopoly on that thing. I’ll talk in a little bit about what the kinds of things are. Why only one “or so few” ways? To avoid a situation where there are three ways of expressing it, and three people express it in all of those three ways, and all get exclusive rights in their particular way. Now there is still no available way for the public to express that thing that we want the public to be able to express without the interference of copyright.